Estudo da elipse e aplicações em órbitas na mecânica clássica e relatividade geral - Yamachita, Ricardo Yoshio (2022)
This work proposes activities involving the ellipse and other curves using polar coordinates. For this, we present a contextualization through the introductory study of orbital dynamics in Classical Mechanics and General Relativity. With that, we introduce curves parameterized in polar coordinates, and relativistic effects such as perihelion precession can be modeled and visualized with the help of computer software.